An iminium ion metabolite hampers the production of the pharmacologically active metabolite of a multikinase inhibitor KW‐2449 in primates: irreversible inhibition of aldehyde oxidase and covalent binding with endogenous proteins. (13th March 2018) - Hosogi, Jun; Ohashi, Rui; Maeda, Hiroshi; Fujita, Kazuhiro; Ushiki, Junko; Kuwabara, Takashi; Yamamoto, Yorihiro; Imamura, Toru
Abstract: We previously reported that KW‐2449, ( E )‐1‐{4‐[2‐(1 H ‐Indazol‐3‐yl)vinyl]benzoyl}piperazine, a novel multikinase inhibitor developed for the treatment of leukemia patients, was oxidized to an iminium ion intermediate by monoamine oxidase B (MAO‐B) and then converted to its oxo‐piperazine form (M1) by aldehyde oxidase (AO). However, it was found that the significant decrease in the pharmacologically active metabolite M1 following repeated administration of KW‐2449 in primates might hamper the effectiveness of the drug. The mechanism underlying this phenomenon was investigated and it was found that the AO activity was inhibited in a time‐dependent manner in vitro under the co‐incubation of KW‐2449 and MAO‐B, while neither KW‐2449 nor M1 strongly inhibited MAO‐B or AO activity. These results clearly suggest that MAO‐B catalysed iminium ion metabolite inhibited AO, prompting us to investigate whether or not the iminium ion metabolite covalently binds to endogenous proteins, as has been reported with other reactive metabolites as a cause for idiosyncratic toxicity. The association of the radioactivity derived from 14 C‐KW‐2449 with endogenous proteins both in vivo and in vitro was confirmed and it was verified that this covalent binding was inhibited by the addition of sodium cyanide, an iminium ion‐trapping reagent, and pargyline, a MAO‐B inhibitor. These findings strongly suggest that the iminium ion metabolite of KW‐2449 is highly reactive in inhibiting AO irreversibly and binding to endogenous macromolecules covalently.